Способ измерения коэффициента ослабления светового излучения в дисперсных средах - Горячев Б. В. Борис Валентинович; Ларионов В. В. Виталий Васильевич; Могильницкий С. Б. Сергей Борисович; Кутлин А. П.; Савельев Б. А.
опубл. в Б. И., 1987, № 12